Company Life Cycle and Capital Structure of Manufacturing Sector In the Consumer Goods Industry - Sulaeman Rahman Nidar; Rizki Agung Ponco Utomo (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2017)
Determination of the optimal capital structure is to be done by each company Capital structure is the balance or ratio between foreign capital and equity capital. One proxy of capital structure is leverage. The well-known theory in determining the leverage or capital structure is the pecking order theory. This theory explains that the company will use the funds to have a safer risk in advance in the determination of corporate leverage. There are many variables that affect the determination of a company's leverage, so it has not acquired a standard model in determining the leverage or capital structure of the company. One variable that will be added to add an explanation of the determination of a company's leverage is the life cycle proposed by Dickinson (2011). Company life cycle differentiated by the company's cash flow includes cash flow from operating, financing, and investment. This study aims to determine whether the company life cycle that can explain the determination of leverage or capital structure of the company, and find out how the influence of other variables such as profitability, liquidity, size of firm, non debt tax shield, asset tangibility, and growth opportunities for determination of leverage or capital structure of the company. The study was conducted in the consumer goods sector companies in 2012 and 2013. This study uses regression with dummy variables. The results showed that in 2012 and 2013 variable life cycle can be one of the variables that can explain leverage the company's decision. Variables that affect the leverage is profitability, liquidity, non debt tax shield, asset tangibility, and growth opportunities. Variable has no effect on leverage is size of the company.